Preparation process of wear-resistant and alkali-resistant castable
Through layered structure and sol-gel coating technology, the problem of wear-resistant and alkali-resistant castables deteriorate performance in high temperature environments is solved, and the material's wear and alkali resistance is improved, which extends the service life and improves the use of the material. Structural stability.
Patent Information
- Application Number
- CN202411391858.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing wear-resistant and alkali-resistant castables are difficult to maintain alkali-resistant properties when improving wear-resistant properties, and their structures are prone to deterioration in high-temperature environments, affecting their service life.
The castable preparation process with a layered structure is adopted, and the material's wear resistance and alkali resistance are enhanced through the layered distribution of electromelted corundum particles and mullite flakes, combined with sol-gel coating technology and optimized heat treatment parameters. Ensure the stability of the material under complex working conditions.
It significantly improves the wear resistance and alkali resistance of the material, extends the service life, improves crack resistance and structural stability, and ensures high-temperature performance in harsh environments.
Smart Images

Figure BDA0005072643640000091 
Figure BDA0005072643640000101 
Figure BDA0005072643640000102
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting material preparation, in particular to a preparation process of a wear-resistant and alkali-resistant casting material. Background Art
[0002] Wear-resistant and alkali-resistant castable is a high-performance inorganic non-metallic material, which is widely used in high-temperature equipment in chemical, metallurgical, electric power, building materials and other industries. Especially in the environment of dealing with alkaline media, its excellent wear resistance and alkali resistance make it an indispensable protective material.
[0003] Traditionally, castables with this type of performance are usually composed of refractory cement materials and a certain proportion of alkali-resistant enhancers, and are prepared through careful proportioning and scientific processes to achieve the best effect. However, with the continuous improvement of industrial production requirements for material performance, the existing technology still has some unresolved problems in meeting applications under extreme working conditions.
[0004] When improving the alkali resistance of materials, it is often accompanied by a decrease in wear resistance, and vice versa. How to ensure the alkali resistance of castables while improving their wear resistance to adapt to more complex use environments is a major challenge in current technology. In addition, at high temperatures, the structure of castables is prone to change, resulting in performance degradation, especially under conditions of large temperature fluctuations. The stability of the material also becomes a key factor affecting its service life. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a preparation process of wear-resistant and alkali-resistant castable.
[0006] The technical solution of the present invention is: a preparation process of wear-resistant and alkali-resistant castable, comprising the following steps:
[0007] S1. By mass percentage, weigh 10-18% of Ca3SiO5 powder, 5-10% of Ca2SiO4 powder, 5-10% of refractory clay, 1-9% of nano-alumina powder, 2-8% of gallium oxide powder, 2-4% of composite modifier and the remainder of high-alumina clinker to obtain raw material powder;
[0008] S2, introducing the raw material powder described in S1 into a dry mixer for mixing for 15 to 30 minutes to ensure that the components are evenly distributed to obtain a mixture; then adding the mixture into a wet mixer, adding water accounting for 40 to 70% of the raw material powder by mass, and continuously mixing for 10 to 15 minutes to obtain a slurry; using a vibration molding machine to press the slurry into shape to ensure that there are no pores inside the material to obtain a molded slurry;
[0009] S3, the forming slurry described in S2 is divided into component A and component B in a mass ratio of 2 to 3:1, and fused corundum particles accounting for 3 to 10% of component A by mass are taken, and the fused corundum particles are washed and immersed in sol treatment liquid A, and then taken out after standing for 3 to 15 minutes, and then heat-dried in an oven at 50 to 100° C. until the sol is gelled to form a uniform coating, and aged at room temperature for 24 to 30 hours to obtain coating particles, and then heat-treated, and the heat-treated coating particles are evenly stirred with component A to obtain the first main material;
[0010] Take mullite flakes accounting for 3-10% of component B by mass, wash the mullite flakes and soak them in sol treatment solution B, let them stand for 3-10 minutes, then take them out, and then heat dry them in an oven at 50-100°C until the sol gels to form a uniform coating, age them at room temperature for 24-30 hours to obtain a coating flake, and then heat treat them, and stir the heat-treated coating flakes and component B evenly to obtain a second main material;
[0011] S4. The first main material and the second main material described in S3 are mixed and preheated, and then the temperature is increased to 800-850°C at a heating rate of 5-7°C / min, and kept warm for 2-4 hours. Finally, the temperature is increased to 1100-1250°C at a heating rate of 2-4°C / min, and kept warm for 2-4 hours to obtain a wear-resistant and alkali-resistant castable.
[0012] Description: The coated fused corundum particles in the first main material sink due to their high density and are concentrated at the bottom of the castable, thereby enhancing the wear resistance of the contact area with the working surface; the coated mullite flakes in the second main material have a lower density and float to the surface, thereby improving the surface's alkali resistance and corrosion resistance. This layered structure effectively enhances the material's protective performance under complex working conditions; the preparation process of this method effectively enhances the performance of the wear-resistant and alkali-resistant castable by optimizing material selection, processing methods and heat treatment parameters, making it effective in industrial applications, especially in environments that need to withstand both wear and alkaline corrosion.
[0013] Furthermore, the Al2O3 content of the high-alumina clinker in S1 is 85-90%, and the particle size is 1-3 mm; the particle size of the nano alumina powder is 30-50 nm; the particle size of the refractory clay is 0.01-0.05 mm; and the particle size of the gallium oxide powder is 45-55 μm.
[0014] Description: The high Al2O3 content of high-alumina bauxite clinker ensures the high melting point and chemical stability of the material, especially in alkaline environment, and can resist the corrosion of alkali metals. The particle size is 1-3mm: This particle size range provides a good particle gradation, enhances the structural strength and thermal shock resistance of the castable, and is conducive to improving the permeability and thermal stability of the castable; the extremely fine particle size of nano-alumina powder can fill tiny pores, increase the density and hardness of the castable, and significantly improve its wear resistance and corrosion resistance. Nano-alumina powder can improve the interface bonding with other components and enhance The overall mechanical properties and crack resistance of the material, the fine particle size of refractory clay helps to form a denser microstructure, reduce porosity, and improve the density and erosion resistance of the material. Refractory clay, as a binder, enhances the bonding force between the components of the castable and improves the structural stability and wear resistance of the material. The gallium oxide powder has a moderate particle size: it maintains good dispersibility and avoids the sedimentation problem caused by too fine, which helps to form a uniform composite material structure. The addition of gallium oxide powder can improve the alkali resistance of the castable, especially under high temperature conditions, and can effectively resist the erosion of alkaline substances.
[0015] Furthermore, the particle sizes of the Ca3SiO5 powder in S1 are 5-7 μm and 35-45 μm, and the mass ratio of the two particle sizes is 1:9; the particle sizes of the Ca2SiO4 powder are 4-6 μm and 30-40 μm, and the mass ratio of the two particle sizes is 1:6-8.
[0016] Description: By mixing Ca3SiO5 powder and Ca2SiO4 powder of different particle sizes, a more compact and uniform microstructure can be formed. Fine-grained powder can fill the gaps between coarse-grained powders, reduce porosity, and enhance the density and wear resistance of the material; reasonable particle size ratio can improve the rheological properties of the material, making the castable easier to flow and compact during the molding process, improving the molding quality and efficiency. Fine powder helps to improve the fluidity of the slurry, while coarse powder helps to increase the structural strength; mixing powders of different particle sizes can enhance the mechanical properties of the castable, such as compressive strength and flexural strength. The combination of fine powder and coarse powder in a certain proportion can optimize the stress distribution of the material and improve its impact resistance and crack resistance; Ca3SiO5 and Ca2SiO4 powders act as chemical stabilizers in the castable. By controlling the particle size ratio, the alkali resistance and corrosion resistance of the material can be enhanced. Fine powder is easier to participate in chemical reactions, improving the chemical activity and durability of the material.
[0017] Furthermore, the composition of the composite modifier described in S1 is: 15-35wt% silane coupling agent and the balance nano-silicon dioxide.
[0018] Description: Silane coupling agents can form chemical bonds between inorganic materials such as nano-silica and organic materials in castables, significantly improving the interfacial bonding between the two, thereby enhancing the overall structural strength and durability of the castable; the high specific surface area and surface energy of nano-silica usually lead to its agglomeration in organic media. The use of silane coupling agents can effectively reduce this agglomeration and improve the dispersibility of nanoparticles in the castable matrix, thereby improving the uniformity and performance of the material; nano-silica particles modified by silane coupling agents can be better dispersed in the castable, and these particles can form a layer of reinforced network structure on the surface of the material, improving the wear resistance and chemical corrosion resistance of the castable.
[0019] Furthermore, the particle size of the fused corundum particles is 1 to 8 mm; the average length and width of the mullite flakes are 0.5 to 2 mm, and the thickness is 0.5 to 1.5 mm.
[0020] Description: Due to its high hardness and wear resistance, fused corundum particles can significantly improve the wear resistance of castables. The particle size range of 1 to 8 mm can form a multi-level protection to effectively resist wear. Mullite flakes can form a dense protective layer on the surface of the castable to improve alkali resistance and corrosion resistance. The proportion of components A and B ensures the sinking of fused corundum particles and the floating of mullite flakes, forming a reasonable structural distribution, that is, high wear resistance and high alkali resistance materials are located on the surface to maximize performance. The large particle size of fused corundum combined with mullite flakes can reduce the porosity inside the castable and improve the compactness and stability of the structure.
[0021] Furthermore, the preparation method of the sol treatment liquid A in S3 is: by mass percentage, at room temperature, 10-20% TEOS, 10-20% deionized water, 1-5% ammonia water and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid A; the preparation method of the sol treatment liquid B is: by mass percentage, at room temperature, 10-20% Zr(OC2H5)4, 10-20% deionized water, 1-5% nitric acid and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid B.
[0022] Description: Sol-gel technology can produce uniform and highly adhesive coatings because the sol can penetrate into the tiny pores of the material to form a continuous and uniform coating, which improves the surface properties of the material; TEOS, i.e. tetraethoxysilane, is hydrolyzed and polycondensed under the catalysis of ammonia water to form a silicon dioxide coating with high chemical stability, which enhances the wear resistance and corrosion resistance of the fused corundum particles; Zr(OC2H5)4, i.e. tetraethoxyzirconium, forms a zirconium oxide coating under the catalysis of nitric acid, which improves the high temperature resistance and alkali resistance of the mullite flakes; the sol-gel coating has a high bonding strength with the base material, which can effectively improve the interface bonding, reduce the stress concentration at the interface, and improve the overall mechanical properties of the material.
[0023] Further, the heat treatment method of the coating particles in S3 is: pre-sintering the coating particles at 400-600°C for 1-2 hours to remove organic matter in the sol. Then calcining the coating particles at 1000-1200°C for 2-4 hours; the heat treatment method of the coating flakes is: pre-sintering the coating flakes at 400-600°C for 1-2 hours to remove organic matter in the sol. Then calcining the coating flakes at 1200-1400°C for 2-4 hours.
[0024] Description: In the pre-burning stage at 400-600℃, the residual organic matter in the sol treatment solution can be effectively removed to prevent the generation of pores or cracks during subsequent high-temperature treatment, ensuring the integrity of the coating and the density of the material; during the calcination process of the fused corundum particles at 1000-1200℃, the bonding force between the coating and the substrate material is further enhanced, improving the chemical stability and wear resistance of the coating; at the calcination temperature of 1200-1400℃, the crystal phase transformation of the mullite flakes is completed, forming a more stable crystal phase structure, improving high temperature resistance and alkali resistance.
[0025] Furthermore, the preheating method in S4 is: heating the first main material and the second main material from room temperature to 90-100° C. at a heating rate of 9-12° C. / min, and then keeping the temperature for 1-2 hours.
[0026] Note: Preheating can reduce the thermal stress generated by the material during subsequent high-temperature treatment, because the temperature change of the material during heating and cooling is more gentle, which helps to improve the overall stability of the molded body; through preheating, the moisture and organic matter inside the material can be removed more effectively, reducing pores and defects during sintering, thereby improving the density and mechanical properties of the final product.
[0027] The beneficial effects of the present invention are:
[0028] The method of the present invention significantly improves the wear resistance of the material through the high hardness of the fused corundum particles and the reinforcing effect of the coating; through the alkali resistance of the mullite flakes and the synergistic effect of the coating, the ability of the mullite flakes to resist alkaline corrosion, especially the protective effect of the surface layer, is enhanced; through multi-step treatments such as dry mixing, wet mixing and vibration molding, the uniform dispersion of the raw materials and the density of the castable are ensured, the internal pores are reduced, and the structural stability and thermal shock resistance of the material are improved; by using preheating treatment and staged heating and insulation, the thermal stress of the material is effectively controlled, the combination of the coating and the substrate is promoted, and the high-temperature performance and service life of the castable are improved; by using the sol-gel coating technology, not only the surface properties of the particles and flakes are enhanced, but also a uniform and stable coating is formed by heat treatment, the interface bonding of the material is improved, and the overall performance is improved; through the above process, the castable maintains good wear and alkali resistance while also improving the crack resistance and structural stability, thereby extending the service life of the material in harsh environments and enhancing the wear resistance of the castable surface. DETAILED DESCRIPTION
[0029] Embodiment 1: A process for preparing a wear-resistant and alkali-resistant castable, comprising the following steps:
[0030] S1. Weigh 14% of Ca3SiO5 powder, 7.5% of Ca2SiO4 powder, 7.5% of refractory clay, 5% of nano-alumina powder, 5% of gallium oxide powder, 3% of composite modifier and the remainder of high-alumina clinker to obtain raw material powder.
[0031] The Al2O3 content of the high-alumina clinker is 87.5%, and the particle size is 2-2.5 mm; the particle size of the nano-alumina powder is 36-40 nm; the particle size of the refractory clay is 0.02-0.03 mm; the particle size of the gallium oxide powder is 48-50 μm;
[0032] The particle sizes of the Ca3SiO5 powder are 6-6.5 μm and 38-40 μm, and the mass ratio of the two particle sizes is 1:9; the particle sizes of the Ca2SiO4 powder are 5-5.5 μm and 35-37 μm, and the mass ratio of the two particle sizes is 1:7;
[0033] The composite modifier comprises: 25wt% of silane coupling agent and the balance of nano silicon dioxide;
[0034] S2, introducing the raw material powder described in S1 into a dry mixer for mixing for 22.5 minutes, ensuring that the components are evenly distributed, and obtaining a mixture; then adding the mixture into a wet mixer, adding water accounting for 55% of the mass ratio of the raw material powder, and continuously mixing for 12.5 minutes to obtain a slurry; using a vibration molding machine to press the slurry into a shape, ensuring that there are no pores inside the material, and obtaining a molded slurry;
[0035] S3, the forming slurry described in S2 is divided into component A and component B in a mass ratio of 2.5:1, and fused corundum particles accounting for 6.5% of component A by mass are taken, and the fused corundum particles are washed and immersed in sol treatment liquid A, and then taken out after standing for 9 minutes, and then heat-dried in an oven at 75°C until the sol gels to form a uniform coating, and aged at room temperature for 27 hours to obtain coating particles, and then heat-treated, and the heat-treated coating particles and component A are evenly stirred to obtain the first main material;
[0036] Take a mullite sheet with a mass ratio of 6.5% of component B, wash the mullite sheet and soak it in sol treatment liquid B, let it stand for 6.5 minutes, then take it out, and then heat dry it in an oven at 75°C until the sol gels to form a uniform coating, age it at room temperature for 27 hours to obtain a coating sheet, and then heat treat it, and stir the heat-treated coating sheet and component B evenly to obtain the second main material;
[0037] The particle size of the fused corundum particles is 4.5-5 mm; the average length and width of the mullite flakes are 1-1.5 mm, and the thickness is 1-1.2 mm;
[0038] The preparation method of the sol treatment liquid A is as follows: by mass percentage, at room temperature, 15% TEOS, 15% deionized water, 2.5% ammonia water and the rest ethanol are mixed, and the mixture is stirred until the solution is clear, thereby obtaining the sol treatment liquid A; the preparation method of the sol treatment liquid B is as follows: by mass percentage, at room temperature, 15% Zr(OC2H5)4, 15% deionized water, 2.5% nitric acid and the rest ethanol are mixed, and the mixture is stirred until the solution is clear, thereby obtaining the sol treatment liquid B;
[0039] The heat treatment method of the coating particles is: pre-sintering the coating particles at 500°C for 1.5 hours to remove organic matter in the sol. Then calcining the coating particles at 1100°C for 3 hours; the heat treatment method of the coating flakes is: pre-sintering the coating flakes at 500°C for 1.5 hours to remove organic matter in the sol. Then calcining the coating flakes at 1300°C for 3 hours;
[0040] S4, the first main material and the second main material described in S3 are mixed and preheated, then heated to 825° C. at a heating rate of 6° C. / min, kept warm for 3 hours, and finally heated to 1200° C. at a heating rate of 3° C. / min, kept warm for 3 hours, to obtain a wear-resistant and alkali-resistant castable;
[0041] The preheating method is: heating the first main material and the second main material from room temperature to 95° C. at a heating rate of 10.5° C. / min, and then keeping the temperature for 1.5 hours.
[0042] Example 2: This example is different from Example 1 in that 10% of Ca3SiO5 powder, 5% of Ca2SiO4 powder, 5% of refractory clay, 1% of nano alumina powder, 2% of gallium oxide powder, 2% of composite modifier and the remainder of high alumina clinker are weighed to obtain raw material powder.
[0043] Example 3: This example is different from Example 1 in that 18% of Ca3SiO5 powder, 10% of Ca2SiO4 powder, 10% of refractory clay, 9% of nano alumina powder, 8% of gallium oxide powder, 4% of composite modifier and the remainder of high alumina clinker are weighed to obtain raw material powder.
[0044] Example 4: The difference between this example and Example 1 is that the raw material powder described in S1 is introduced into a dry mixer for mixing, and the mixing time is 15 minutes to ensure that the components are evenly distributed to obtain a mixture; then the mixture is added to a wet mixer, and water accounting for 40% of the mass ratio of the raw material powder is added, and mixing is continued for 10 minutes to obtain a slurry.
[0045] Example 5: The difference between this example and Example 1 is that the raw material powder described in S1 is introduced into a dry mixer for mixing, and the mixing time is 30 minutes to ensure that the components are evenly distributed to obtain a mixture; then the mixture is added to a wet mixer, and water accounting for 70% of the mass ratio of the raw material powder is added, and mixing is continued for 15 minutes to obtain a slurry.
[0046] Example 6: The difference between this example and Example 1 is that the forming slurry described in S2 is divided into component A and component B in a mass ratio of 2:1, and fused corundum particles accounting for 3% of component A by mass are taken. The fused corundum particles are cleaned and immersed in sol treatment liquid A, and then taken out after standing for 3 minutes. They are then heat-dried in an oven at 50°C until the sol gels to form a uniform coating, and aged at room temperature for 24 hours to obtain coated particles.
[0047] Example 7: The difference between this example and Example 1 is that the forming slurry described in S2 is divided into component A and component B in a mass ratio of 3:1, and the fused corundum particles accounting for 10% of the mass ratio of component A are taken. The fused corundum particles are cleaned and immersed in sol treatment liquid A, and then taken out after standing for 15 minutes. Then, they are heat-dried in an oven at 100°C until the sol gels to form a uniform coating, and aged at room temperature for 30 hours to obtain coated particles.
[0048] Example 8: The difference between this example and Example 1 is that: take mullite flakes accounting for 3% of component B by mass, wash the mullite flakes and soak them in sol treatment liquid B, let them stand for 3 minutes and then take them out, and then heat dry them in an oven at 50°C until the sol gels to form a uniform coating, and age them at room temperature for 24 hours to obtain a coating sheet.
[0049] Example 9: The difference between this example and Example 1 is that: take mullite flakes accounting for 10% of component B by mass, wash the mullite flakes and soak them in sol treatment liquid B, let them stand for 10 minutes and then take them out, and then heat dry them in an oven at 100°C until the sol gels to form a uniform coating, and age them at room temperature for 30 hours to obtain a coating sheet.
[0050] Example 10: The difference between this example and Example 1 is that the first main ingredient and the second main ingredient described in S3 are mixed and preheated, then heated to 800°C at a heating rate of 5°C / min, kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 2°C / min, kept warm for 2 hours, to obtain a wear-resistant and alkali-resistant castable.
[0051] Example 11: The difference between this example and Example 1 is that the first main ingredient and the second main ingredient described in S3 are mixed and preheated, then heated to 850°C at a heating rate of 7°C / min, kept warm for 4 hours, and finally heated to 1250°C at a heating rate of 4°C / min, kept warm for 4 hours, to obtain a wear-resistant and alkali-resistant castable.
[0052] Example 12: The difference between this example and Example 1 is that: the particle size of the Ca3SiO5 powder in S1 is 5-5.5μm and 35-38μm, and the mass ratio of the two particle sizes is 1:9; the particle size of the Ca2SiO4 powder is 4-4.5μm and 30-35μm, and the mass ratio of the two particle sizes is 1:6.
[0053] Example 13: The difference between this example and Example 1 is that: the particle size of the Ca3SiO5 powder in S1 is 6.5-7μm and 43-45μm, and the mass ratio of the two particle sizes is 1:9; the particle size of the Ca2SiO4 powder is 5.5-6μm and 37-40μm, and the mass ratio of the two particle sizes is 1:8.
[0054] Example 14: This example is different from Example 1 in that: the mass ratio of component A and component B in S3 is 2:1, the particle size of the fused corundum particles is 1-2 mm; the average length and width of the mullite flakes are 0.5-1 mm, and the thickness is 0.5-1 mm.
[0055] Example 15: This example is different from Example 1 in that: the mass ratio of component A and component B in S3 is 3:1, the particle size of the fused corundum particles is 7-8 mm; the average length and width of the mullite flakes are 1.5-2 mm, and the thickness is 1-1.5 mm.
[0056] Example 16: The difference between this example and Example 1 is that: The preparation method of the sol treatment liquid A described in S3 is: by mass percentage, at room temperature, 10% TEOS, 10% deionized water, 1% ammonia water and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid A; The preparation method of the sol treatment liquid B is: by mass percentage, at room temperature, 10% Zr(OC2H5)4, 10% deionized water, 1% nitric acid and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid B.
[0057] Example 17: The difference between this example and Example 1 is that: The preparation method of the sol treatment liquid A described in S3 is: by mass percentage, at room temperature, 20% TEOS, 20% deionized water, 5% ammonia water and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid A; The preparation method of the sol treatment liquid B is: by mass percentage, at room temperature, 20% Zr(OC2H5)4, 20% deionized water, 5% nitric acid and the rest ethanol are mixed, and the mixture is stirred until the solution becomes clear to obtain the sol treatment liquid B.
[0058] Example 18: This example is different from Example 1 in that: the heat treatment method of the coating particles in S3 is: pre-sintering the coating particles at 400°C for 1 hour to remove organic matter in the sol. Then calcining the coating particles at 1000°C for 2 hours; the heat treatment method of the coating flakes is: pre-sintering the coating flakes at 400°C for 1 hour to remove organic matter in the sol. Then calcining the coating flakes at 1200°C for 2 hours.
[0059] Example 19: This example is different from Example 1 in that: the heat treatment method of the coating particles in S3 is: pre-sintering the coating particles at 600°C for 2 hours to remove organic matter in the sol. Then calcining the coating particles at 1200°C for 4 hours; the heat treatment method of the coating flakes is: pre-sintering the coating flakes at 600°C for 2 hours to remove organic matter in the sol. Then calcining the coating flakes at 1400°C for 4 hours.
[0060] Comparative Example 1: Taking Example 1 as a reference, the molding slurry is directly subjected to radial preheating and heat treatment in step S4 without performing step S3 to obtain a casting material.
[0061] Control Example 2: Taking Example 1 as a reference, the particle sizes of the Ca3SiO5 powder in S1 are 8-9 μm and 50-53 μm, and the mass ratio of the two particle sizes is 1:5; the particle sizes of the Ca2SiO4 powder are 7-8 μm and 45-48 μm, and the mass ratio of the two particle sizes is 1:4.
[0062] Comparative Example 3: With reference to Example 1, the mass ratio of component A to component B in S3 is 1:1, the particle size of the fused corundum particles is 0.5-1 mm; the average length and width of the mullite flakes are 0.2-0.3 mm, and the thickness is 0.1-0.5 mm.
[0063] Control Example 4: Taking Example 1 as a reference, the first main ingredient and the second main ingredient described in S3 are mixed and preheated, then heated to 900°C at a heating rate of 8°C / min, kept warm for 6 hours, and finally heated to 1300°C at a heating rate of 5°C / min, kept warm for 1 hour, to obtain a wear-resistant and alkali-resistant castable.
[0064] Control Example 5: With reference to Example 1, the preparation method of the sol treatment liquid A described in S3 is as follows: by mass percentage, at room temperature, 30% TEOS, 25% deionized water, 0.5% ammonia water and the remainder ethanol are mixed, and stirred until the solution is clear to obtain sol treatment liquid A.
[0065] Control Example 6: With reference to Example 1, the preparation method of the sol treatment liquid B is as follows: by mass percentage, at room temperature, 30% Zr(OC2H5)4, 25% deionized water, 6% nitric acid and the remainder ethanol are mixed, and stirred until the solution is clear to obtain sol treatment liquid B.
[0066] In order to explore the performance of wear-resistant and alkali-resistant castables produced in Examples 1, 6 to 17 and Comparative Examples 1 to 6, the main materials were determined according to the experimental formula and 19 groups of samples were prepared for testing. The test results are shown in Table 1. The specific exploration is as follows:
[0067] Table 1 Performance test results of samples of Examples 1, 6 to 9 and Comparative Example 1
[0068]
[0069] 1. Investigate the influence of the process parameters of heat treatment in step S4 on the properties of castables:
[0070] As shown in Table 1, by comparing Examples 1, 6 to 9 and Control Example 1, it can be seen that: at 110°C, 4h environment, the strength range of Examples 1, 6 to 9 is 10 to 15MPa, among which Example 1 has the highest strength; Control Example 1 has the lowest strength, which is 10MPa, indicating that the structural strength of Control Example 1 is relatively low in the initial stage of hardening; at 1400°C, 4h environment, the strength of all samples is significantly improved, ranging from 16 to 19MPa, and the structural density and strength of the material will increase at high temperature. Example 1 performs best, with better structural stability under high temperature conditions. All samples have high corrosion resistance in high temperature alkaline environments, and the wear values of the strength of Examples 1, 6 to 9 range from 3.2 to 3.8cm 3 , has good wear resistance under high temperature and alkaline conditions; the wear value of control example 1 is the highest, which is 4.1cm 3 The wear performance of the control example 1 in a high temperature alkaline environment is poor; it can be seen that the castable prepared by using the process parameters of Example 1 not only has the highest initial temperature strength and high temperature strength, but also has the best wear resistance.
[0071] Table 2 Performance test results of samples of Examples 10, 11 and Comparative Example 4
[0072]
[0073] 2. Investigate the influence of S4 heat treatment process parameters on castable properties:
[0074] As shown in Table 2, by comparing Examples 10, 11 and Control Example 4, it can be seen that: at a temperature of 110°C for 4h, the strengths of both Example 10 and Control Example 4 are 14MPa, while the strength of Example 11 is slightly lower, 12MPa. In the initial stage of material hardening, the strength of Example 11 is slightly lower; at high temperatures, the structural density and strength of Example 10 are better; the strength of Example 11 is 16MPa, which is lower than Example 10 but higher than Control Example 4, and the performance of Example 11 at high temperatures is still better than that of Control Example 4; the three groups of samples have excellent corrosion resistance; the wear resistance of Example 10 and Example 11 is equivalent; the wear value of Control Example 4 is 3.7cm 3 The wear resistance is relatively poor. It can be seen that the process parameters of S4 heat treatment have a certain influence on the performance of castables.
[0075] Table 3 Performance test results of samples of Examples 12, 13 and Comparative Example 2
[0076]
[0077] 3. Investigate the influence of the process parameters of Ca3SiO5 powder particle size on the performance of castables:
[0078] As shown in Table 3, by comparing Examples 12, 13 and Control Example 2, it can be seen that the anti-segregation strength of Control Example 2 is lower than that of Examples 12 and 13; the corrosion resistance of the three groups of samples is excellent; the wear values of Examples 12 and 13 are similar; the wear value of Control Example 2 is 4.3 cm 3 , higher than Examples 12 and 13, and its wear resistance is relatively poor; Example 12 performs best in all tests, with the highest anti-dialysis strength and lower wear value. Although the anti-dialysis strength of Example 13 is slightly lower than that of Example 12, its wear resistance is comparable to that of Example 12. It can be seen that the process parameters of Ca3SiO5 powder particle size have a certain influence on the performance of the castable.
[0079] Table 4 Performance test results of samples of Examples 14, 15 and Comparative Example 3
[0080]
[0081] 4. Investigate the influence of process parameters of component A and component B on castable properties:
[0082] As shown in Table 4, by comparing Examples 14, 15 and Control Example 3, it can be seen that Example 15 performs best in terms of anti-sedimentation strength and wear resistance at high temperatures. Not only does the strength increase significantly with the increase in temperature, but the wear value is also the lowest, indicating that it has better stability and wear resistance under high temperature and alkaline conditions; the corrosion resistance of the three groups of samples is excellent; compared with Control Example 3, Example 14 has a higher strength at high temperatures, although the wear value is similar to that of Control Example 3; while Control Example 3 performs poorly in both anti-sedimentation strength and wear resistance, especially in terms of wear resistance, the wear value is significantly higher than that of Examples 14 and 15, indicating that it is easily damaged under high temperature and alkaline conditions; it can be seen that the process parameters of the composition of component A and component B have a certain influence on the performance of the castable.
[0083] Table 5 Performance test results of samples of Examples 16, 17 and Comparative Examples 5, 6
[0084]
[0085]
[0086] 5. Investigate the influence of the ratio parameters of sol treatment liquid A and sol treatment liquid B on the performance of castables
[0087] As shown in Table 5, by comparing Examples 16 and 17 with Control Examples 5 and 6, it can be seen that: the anti-sedimentation strength of Example 17 at high temperature is slightly higher than that of Example 16, and the wear value is only slightly higher than that of Example 16, showing good high temperature performance and wear resistance; the corrosion resistance of the four groups of samples is excellent; Examples 16 and 17 perform better in wear resistance, especially Example 16, which has the lowest wear value, showing better wear resistance; the initial temperature anti-sedimentation strength of Control Examples 5 and 6 is similar to that of the example samples, but Control Example 5 has the highest anti-sedimentation strength at high temperature and a higher wear value, indicating that its performance under high temperature conditions is strong but its wear resistance is poor; Examples 16 and 17 perform well in wear resistance and high temperature anti-sedimentation strength, while Control Examples 5 and 6 have advantages in some properties but relatively poor wear resistance. It can be seen that the ratio parameters of sol treatment liquid A and sol treatment liquid B have a certain influence on the performance of the castable.
Claims
1. A process for preparing a wear-resistant and alkali-resistant castable, characterized in that: The following steps are involved: S1. By mass percentage, weigh 10-18% of Ca3SiO5 powder, 5-10% of Ca2SiO4 powder, 5-10% of refractory clay, 1-9% of nano-alumina powder, 2-8% of gallium oxide powder, 2-4% of composite modifier and the remainder of high-alumina clinker to obtain raw material powder; S2, introducing the raw material powder described in S1 into a dry mixer for mixing for 15 to 30 minutes to ensure that the components are evenly distributed to obtain a mixture; then adding the mixture into a wet mixer, adding water accounting for 40 to 70% of the raw material powder by mass, and continuously mixing for 10 to 15 minutes to obtain a slurry; using a vibration molding machine to press the slurry into shape to ensure that there are no pores inside the material to obtain a molded slurry; S3, the forming slurry described in S2 is divided into component A and component B in a mass ratio of 2 to 3:1, and fused corundum particles accounting for 3 to 10% of component A by mass are taken, and the fused corundum particles are washed and immersed in sol treatment liquid A, and then taken out after standing for 3 to 15 minutes, and then heat-dried in an oven at 50 to 100° C. until the sol is gelled to form a uniform coating, and aged at room temperature for 24 to 30 hours to obtain coating particles, and then heat-treated, and the heat-treated coating particles are evenly stirred with component A to obtain the first main material; Take mullite flakes accounting for 3-10% of component B by mass, wash the mullite flakes and soak them in sol treatment solution B, let them stand for 3-10 minutes, then take them out, and then heat dry them in an oven at 50-100°C until the sol gels to form a uniform coating, age them at room temperature for 24-30 hours to obtain a coating flake, and then heat treat them, and stir the heat-treated coating flakes and component B evenly to obtain a second main material; S4. The first main material and the second main material described in S3 are mixed and preheated, and then the temperature is increased to 800-850°C at a heating rate of 5-7°C / min, and kept warm for 2-4 hours. Finally, the temperature is increased to 1100-1250°C at a heating rate of 2-4°C / min, and kept warm for 2-4 hours to obtain a wear-resistant and alkali-resistant castable.
2. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: S1 The Al2O3 content of the high-alumina clinker is 85-90%, and the particle size is 1-3 mm; the particle size of the nano-alumina powder is 30-50 nm; the particle size of the refractory clay is 0.01-0.05 mm; and the particle size of the gallium oxide powder is 45-55 μm.
3. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: S1 The particle sizes of the Ca3SiO5 powder are 5-7μm and 35-45μm, and the mass ratio of the two particle sizes is 1:9; the particle sizes of the Ca2SiO4 powder are 4-6μm and 30-40μm, and the mass ratio of the two particle sizes is 1:6-8.
4. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: The composition of the composite modifier described in S1 is: 15-35wt% silane coupling agent and the balance nano silicon dioxide.
5. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: S3 The particle size of the fused corundum particles is 1 to 8 mm; the average length and width of the mullite flakes are 0.5 to 2 mm, and the thickness is 0.5 to 1.5 mm.
6. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: S3 The preparation method of the sol treatment liquid A is: by mass percentage, at room temperature, mix 10-20% TEOS, 10-20% deionized water, 1-5% ammonia water and the rest ethanol, and stir until the solution is clear to obtain sol treatment liquid A; the preparation method of the sol treatment liquid B is: by mass percentage, at room temperature, mix 10-20% Zr(OC2H5)4, 10-20% deionized water, 1-5% nitric acid and the rest ethanol, and stir until the solution is clear to obtain sol treatment liquid B.
7. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: S3 The heat treatment method of the coating particles is: pre-sintering the coating particles at 400-600°C for 1-2 hours, and then calcining the coating particles at 1000-1200°C for 2-4 hours; the heat treatment method of the coating flakes is: pre-sintering the coating flakes at 400-600°C for 1-2 hours, and then calcining the coating flakes at 1200-1400°C for 2-4 hours.
8. A process for preparing a wear-resistant and alkali-resistant castable according to claim 1, characterized in that: The preheating method of S4 is: heating the first main material and the second main material from room temperature to 90-100° C. at a heating rate of 9-12° C. / min, and then keeping the temperature for 1-2 hours.
Citation Information
Patent Citations
Silicasol-combined corundum castable and method for preparing wear-resistant precast pieces
CN101602595A
Composite castable refractory
CN102491771A
Alkali-resistant, wear-resistant and erosion-resistant castable and preparation method thereof
CN117362012A
Liquid binding agent for environment-friendly refractory material and preparation method of liquid binding agent
CN118530033A
Titanium composite corundum silicon carbide wear-resistant castable material for kiln outlet of cement kiln, and preparation method therefor
WO2023098567A1
Cited By
Low-friction-resistance coating of grounding grouting pipeline and preparation method of low-friction-resistance coating
CN122080676A